The next generation of corporate universities : (Pfeiffer, 2007)
Land Development for Civil Engineers provides essential facts and recommendations for bringing the nonstructural features of a land development project to successful completion. Regulations, standards, and permit data have all been thoroughly updated, including EPA General Stormwater Permits and the agency's rulings on water supply, ADA considerations, American Concrete Pipe Association bedding requirements, wetland permitting changes, and other pertinent information. This single-source reference covers all engineering, legislative, and administrative concerns, including design procedures, construction contracts, development guidelines, and final inspections. New techniques for project management, including use of intranet and extranet management tools on the Internet, are featured, in addition to the latest material on: Soil remediation and brownfield development; GPS use and new surveying techniques; Streetscaping; Developments in design-build methods; Photogrammetric surveys and GIS use in area and site planning.